2022
DOI: 10.1101/2022.09.23.22280215
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ARCliDS: A Clinical Decision Support System for AI-assisted Decision-Making in Response-Adaptive Radiotherapy

Abstract: Background: Involvement of many variables, uncertainty in treatment response, and inter-patient heterogeneity challenge objective decision-making in dynamic treatment regime (DTR) in oncology. Advanced machine learning analytics in conjunction with information-rich dense multi-omics data have the ability to overcome such challenges. We have developed a comprehensive artificial intelligence (AI)-based optimal decision-making framework for assisting oncologists in DTR. In this work, we demonstrate the proposed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…We found that for NSCLC out of 41 total decision adjustments, 31 (76%) increased and 10 (24%) decreased both TCP and NTCP, whereas for HCC out of 34 total decision adjustments, 9 (26%) increased and 25 (74%) decreased both TCP and NTCP. Note that the simultaneous increase/decrease in TCP and NTCP is by design 22 which was added into the modeling to follow the radiobiological principle that states that increasing/decreasing radiation dose increases/decreases both TCP and NTCP. Since the clinical goal of RT is to maximize TCP while minimizing NTCP, the observation indicates that most of the decisions were adjusted to achieve higher TCP in NSCLC patients and lower NTCP in HCC patients.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We found that for NSCLC out of 41 total decision adjustments, 31 (76%) increased and 10 (24%) decreased both TCP and NTCP, whereas for HCC out of 34 total decision adjustments, 9 (26%) increased and 25 (74%) decreased both TCP and NTCP. Note that the simultaneous increase/decrease in TCP and NTCP is by design 22 which was added into the modeling to follow the radiobiological principle that states that increasing/decreasing radiation dose increases/decreases both TCP and NTCP. Since the clinical goal of RT is to maximize TCP while minimizing NTCP, the observation indicates that most of the decisions were adjusted to achieve higher TCP in NSCLC patients and lower NTCP in HCC patients.…”
Section: Resultsmentioning
confidence: 99%
“…Such AI behavior can be attributed to the training data distribution where the outcome class imbalance was very extreme, i.e. 95 out of 99 patients showed local control ( Table S10 in Niraula et al 22 ). Whereas higher local control is a clinically desirable endpoint and reflects the fact that SBRT is highly successful in treating HCC, it affects the model sensitivity of outcome prediction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations